The hotspots and publication trends in glioblastoma and CAR-T immunotherapy: A bibliometric analysis - Zhaoming Song; Chen Yang; Jingyu Gu; Ruisi Qu; Yun Xie; Yanao Guo; Xun Nong; Zhouqing Chen; Zhong Wang (Human Vaccines & Immunotherapeutics)
In recent years, chimeric antigen receptor T cell (CAR-T) immunotherapy has made considerable progress in the treatment of glioblastoma. The aim of this study was to comprehensively explore the prospects and future trends of CAR-T immunotherapy for glioblastoma through systematic bibliometric analysis. Publications pertaining to glioblastoma and CAR-T immunotherapy from 2008 to 2024 were extracted from the Web of Science Core Collection. Utilizing VOSviewer (version 1.6.20), CiteSpace (version 6.3.R1), and R 4.3.3, this study concentrated on evaluating contributions from countries, institutions, authors, and journals, while also identifying research hotspots and emerging trends. A total of 570 publications were identified, demonstrating an annual growth rate of 31.71%. The USA led the field with 269 publications, followed by China (113). The University of Pennsylvania, Harvard University, and the University of California System emerged as the most prolific institutions. Frontiers in Immunology published the most articles (42), while Clinical Cancer Research garnered the highest number of citations (2,867). Recent keyword bursts (2022–2024) underscored an increasing focus on combination therapy approaches and outcomes, particularly emphasizing “radiotherapy” (strength 3.49), “solid tumor” (strength 3.49), and “efficacy” (strength 2.79). In recent years, research on CAR-T immunotherapy for glioblastoma has gradually shifted from the exploration of basic mechanisms to the application of clinical combination therapy, and this shift in research direction indicates that CAR-T immunotherapy has a relatively mature technology and great clinical translation potential. In the coming years, CAR-T immunotherapy is expected to usher in a golden era and benefit more patients suffering from glioblastoma.